Functional characterization of BbCRASP-2, a distinct outer membrane protein of Borrelia burgdorferi that binds host complement regulators factor H and FHL-1 - Hartmann, Kristina; Corvey, Carsten; Skerka, Christine; Kirschfink, Michael; Karas, Michael; Brade, Volker; Miller, Jennifer C.; Stevenson, Brian; Wallich, Reinhard; Zipfel, Peter F.; Kraiczy, Peter (Molecular microbiology, 2006)
Borrelia burgdorferi, the aetiological agent of Lyme disease, employs sophisticated means to survive in diverse mammalian hosts. Recent studies demonstrated that acquisition of complement regulators factor H and factor H-like protein-1 (FHL-1) allows spirochetes to resist complement-mediated killing. Serum-resistant B. burgdorferi express up to five distinct complement regulator-acquiring surface proteins (CRASPs) that bind factor H and/or FHL-1. In this study we have identified and characterized one of those B. burgdorferi proteins, named BbCRASP-2. BbCRASP-2 is distinct from the four previously identified factor H/FHL-1-binding CRASPs of B. burgdorferi strains. The single copy of the gene encoding BbCRASP-2, cspZ, is located on the linear plasmid lp28-3. BbCRASP-2 is highly divergent from the factor H/FHL-1-binding protein BbCRASP-1 and from members of the factor H-binding Erp (OspE/F-related) protein family. Peptide mapping analysis revealed that the factor H/FHL-1 binding site is discontinuous and it was found that C-terminal truncations abrogate factor H and FHL-1 binding. The predominant BbCRASP-2 binding site of both host complement regulators was mapped to the short consensus repeat 7 (SCR 7). Factor H and FHL-1 bound to BbCRASP-2 maintain cofactor activity for factor I-mediated C3b inactivation and accelerate the decay of the C3 convertase. Expression of BbCRASP-2 in serum-sensitive B. burgdorferi mutant B313 increased resistance to complement-mediated lysis. The characterization of BbCRASP-2 now provides a complete picture of the three diverse complement regulator-binding protein families of B. burgdorferi yielding new insights into the pathogenesis of Lyme disease.
Gesehen am 15.02.2021